Enhanced peroxymonosulfate activation by (NH4)2Mo3S13 for organic pollutant removal: Crucial roles of adsorption and singlet oxygen. Issue 3 (June 2022) - Wang, Qiaodi; Yan, Liangguo; Wang, Le; Zhang, Wei; Guo, Yanxiu; Song, Wen; Li, Xuguang
Abstract: Though sulfide materials have attracted much attentions in sulfate radicals (SO4 – ) based advanced oxidation processes, the catalytic performance and inherent mechanism of ammonium thiomolybdate ((NH4 )2 Mo3 S13 ) activating peroxymonosulfate (PMS) are less studied. In this work, (NH4 )2 Mo3 S13 materials were prepared by the hydrothermal method and applied as the PMS activator to degrade various organic pollutants. The (NH4 )2 Mo3 S13 /PMS system significantly decomposed tetracycline, oxytetracycline, methylene blue, and congo red. However, the degradation of carbamazepine, disodium p-nitrophenyl phosphate, norfloxacin, and sulfamethoxazole was relatively weaker. This selective catalytic performance was attributed to the adsorption affinities of (NH4 )2 Mo3 S13 for organic pollutants. Besides, the exposed Mo(IV) and S on the surface of (NH4 )2 Mo3 S13 were found to be the main active sites for activation of O2 and PMS. Among various active species, singlet oxygen was the crucial active species, while sulfate and hydroxyl radicals played limited roles for the removal of methylene blue in (NH4 )2 Mo3 S13 /PMS system. The findings of this work proved (NH4 )2 Mo3 S13 materials are promising catalyst for organic pollutants removal in advanced oxidation processes. Graphical Abstract: ga1 Highlights: (NH4 )2 Mo3 S13 was efficient as a PMS activator for organic pollutants removal. The catalytic activity of (NH4 )2 Mo3 S13 was mainly due to its adsorption affinity. (NH4 )2 Mo3 S13 could effectively activate O2 and PMS. Mo and S both played important roles in the activation of PMS. 1 O2 was the primary active species involved in pollutants degradation.